2018
DOI: 10.32674/jis.v8i2.116
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural Adaptation of International College Students in the United States

Abstract: The number of international students attending U.S. colleges and universities has increased considerably over the past decade, and the adaptation of these students is an important concern in cross-cultural research. Using survey data collected from a sample of 169 international students attending a U.S. university, this study examines the temporal patterns of students’ psychological and socio-cultural adaptation. Theresults suggest a two-phase U-curved process of psychological adaptation, with the most obvious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 28 publications
1
24
0
8
Order By: Relevance
“…Kegagalan proses adaptasi secara sosial menyebabkan individu mengalami isolasi dengan lingkungan sosial (Y. Y. Kim, 2001), individu juga akan mengalami dampak secara psikologis seperti merasa stres, merasa tertekan (Alemi & Stempel, 2018), gegar budara (culture shock) (Wang et al, 2018), perasaan tidak menyenangkan, dan merasa cemas (Unjore, 2014). Selanjutnya, budaya, bahasa, dan gaya komunikasi yang berbeda secara fisik juga dapat menghambat proses adaptasi para pendatang (Muchura-Theuri & Obuya, 2018).…”
Section: Pendatangunclassified
“…Kegagalan proses adaptasi secara sosial menyebabkan individu mengalami isolasi dengan lingkungan sosial (Y. Y. Kim, 2001), individu juga akan mengalami dampak secara psikologis seperti merasa stres, merasa tertekan (Alemi & Stempel, 2018), gegar budara (culture shock) (Wang et al, 2018), perasaan tidak menyenangkan, dan merasa cemas (Unjore, 2014). Selanjutnya, budaya, bahasa, dan gaya komunikasi yang berbeda secara fisik juga dapat menghambat proses adaptasi para pendatang (Muchura-Theuri & Obuya, 2018).…”
Section: Pendatangunclassified
“…For immigrants around the world, acculturation has been an ongoing process for almost a century. Upon arrival in the new country and during the initial stages of adaptation, immigrants tend to undergo a culture shock which may include confusion, denial and anger (Y. Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In research literature there have been attempts to investigate the strategies that international students use to overcome the challenges of cross-cultural adaptation (Fu et al, 2018;Peng & Wu, 2019;Wang et al, 2018). Russel et al (2010) found that generally there are three patterns of adjusting to host culture: positive and connected, unconnected and stressed, and distressed and risk-taking.…”
Section: Problem Statementmentioning
confidence: 99%